Differential Effects of Rutin and Its Aglycone Quercetin on Cytotoxicity and Chemosensitization of HCT 116 Colon Cancer Cells to Anticancer Drugs 5-Fluorouracil and Doxorubicin - Iva Suman; Alberta Jezidžić; Dorotea Dobrić; Robert Domitrović (Biology)
Background: Rutin and quercetin are natural flavonoids with a variety of beneficial health effects, including anticancer activity. In the present study, we compared cytotoxicity and chemosensitization of human colon cancer HCT116 cells to anticancer drugs 5-fluorouracil (5-FU) and doxorubicin (DOX) by both compounds. Methods: The 2,3-bis(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilide (XTT) test was used to determine cell viability. Western blot and immunofluorescence techniques were employed in the detection of expression of proteins involved in oxidative stress, apoptosis, and autophagy. Results: Quercetin treatment resulted in reduced cell viability compared to rutin at the same dose, suggesting greater cytotoxicity than rutin against HCT116 cells. Quercetin was also a better chemosensitizer of DOX than rutin, further reducing cell viability. However, rutin was a better chemosensitizer of 5-FU than quercetin. All treatments induced apoptosis, with rutin and DOX inducing intrinsic and 5-FU inducing extrinsic apoptotic cell death. Autophagy was induced in all treatments and played a pro-survival role, with the exception of DOX treatment. Different treatment regimens specifically modulated cancer cell signaling pathways involved in the regulation of oxidative stress, apoptosis, and autophagy. Conclusions: The results of the current study suggest that rutin and quercetin, although structural analogs, act as specific modulators of signaling pathways in cancer cells, differentially affecting cancer cell cytotoxicity and chemosensitization to anticancer drugs, based on the presence of a free hydroxyl group at the C-3 position of the flavonoid backbone at quercetin or rutinose in rutin.